2021
DOI: 10.2196/23464
|View full text |Cite
|
Sign up to set email alerts
|

A Patient Decision Aid for Anticoagulation Therapy in Patients With Nonvalvular Atrial Fibrillation: Development and Pilot Study

Abstract: Background Atrial fibrillation (AF) is one of the most common predisposing factors for ischemic stroke worldwide. Because of this, patients with AF are prescribed anticoagulant medications to decrease the risk. The availability of different options for oral anticoagulation makes it difficult for some patients to decide a preferred choice of medication. Clinical guidelines often recommend enhancing the decision-making process of patients by increasing their involvement in health decisions. In partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A similar approach was taken by a Philippine team. Based on focus group discussions and a literature review, they developed an app (not named) to support shared decision-making for or against OAC [ 21 ]. AFib patients use the app as part of their medical consultation to be educated about AFib and the different options regarding OAC.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach was taken by a Philippine team. Based on focus group discussions and a literature review, they developed an app (not named) to support shared decision-making for or against OAC [ 21 ]. AFib patients use the app as part of their medical consultation to be educated about AFib and the different options regarding OAC.…”
Section: Resultsmentioning
confidence: 99%
“…This was demonstrated by studies conducted globally with low TTR (<65%). 1,11,[15][16][17][18][19][20][21][22][23] The problem seems the worst in Africa, as the lowest TTRs were reported in different regions of the continent. 7,20,[24][25][26][27] Similarly, in Ethiopia, only four studies were conducted in government health facilities and reported lower TTRs in the range of 29-38%.…”
Section: Introductionmentioning
confidence: 99%